2017
DOI: 10.1089/jpm.2016.0167
|View full text |Cite
|
Sign up to set email alerts
|

Communication Challenges and Strategies of U.S. Health Professionals Caring for Seriously Ill South Asian Patients and Their Families

Abstract: While providers should avoid stereotyping patients, an awareness of common challenges and adoption of recommended strategies to address these challenges may enhance the provision of culturally responsive person-centered services for seriously ill South Asian patients and their families receiving care in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(56 citation statements)
references
References 21 publications
1
55
0
Order By: Relevance
“…We also showed that network structure and composition, including density, closeness, and proportion kin, were associated with health discussions among South Asians and their network members. Our data lend additional empiric support to prior studies showing that South Asian immigrants rely on close family members for health information and advice [ 45 ]. How these health discussions influence behaviors or health outcomes is an area that has yet to be explored.…”
Section: Discussionsupporting
confidence: 84%
“…We also showed that network structure and composition, including density, closeness, and proportion kin, were associated with health discussions among South Asians and their network members. Our data lend additional empiric support to prior studies showing that South Asian immigrants rely on close family members for health information and advice [ 45 ]. How these health discussions influence behaviors or health outcomes is an area that has yet to be explored.…”
Section: Discussionsupporting
confidence: 84%
“…Often, caregivers used to ignore their own physical health and struggled with normal life due to the demands of their role as caregivers (Chattoo and Ahmad, 2008; Shanmugasundaram, 2015; Somerville, 2001). Religious beliefs were found to be a common coping resource used by family caregivers (Khosla et al, 2017; Kristiansen et al, 2014; Somerville, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Indirect communication approaches also have been found to be the preferred EOL care discussion strategy among various ethnic groups, such as Southeast Asians. 13,24,25 In a systematic review of indirect patient communication about EOL, the authors found that this approach was a "gentle way of 'pushing at the door' of the topics-which some patients take up and some deflect." 26 Building advance care planning inquiry into the check-in procedures builds indirect communication into health-care systems.…”
Section: Discussionmentioning
confidence: 99%